Assuring Quality amidst Political Intrigue in Higher Education Institutions - Zami Atibuni, Dennis; Kani Olema, David (East African Journal of Education Studies, 2021)
This article provides an anatomical analysis of the political intrigue within quality assurance and management mechanisms of higher education institutions in East Africa. Actionable strategies are hence proposed for circumventing the negative effects of such intrigue in order to ensure quality service delivery within the institutions while respecting the need for diversity and innovative practices in research and education. We recognize that the primary responsibility for quality assurance and quality management lies with the higher education institutions themselves, rather than with any outside body. The article therefore discusses issues of autonomy internal to the institutions and those external - between the institutions and regulatory cum oversight bodies that have perpetually riddled the efficiency of quality enhancement. The article draws its data and information from international, national, and institutional policies as well as refereed studies on quality assurance and quality management, especially those highlighting political intrigue in the processes. It has been observed that quality assurance of higher education processes is desired to enhance quality in the response of higher education to labour market needs. However, the article reveals the existence of immense negative politicking and intrigue in the quality assurance processes in higher education institutions in East Africa which are responsible for compromising the quality of services delivered by the institutions. It is argued that being an indicator for organisational performance, the continuous monitoring and enhancing of quality of higher education should be the primary goal and objective of all stakeholders of higher education in East Africa, meaning that quality assurance processes should be embedded in the conducting of the routine business of the institutions.
Keywords: Autonomy; Intrigue; Politics; Quality Assurance; Quality Management